Multiple Clinical Findings on The Tongue: Variants of Normal or Pathologic Condition? (A Case Report): Temuan Klinis Multipel pada Lidah: Variasi Normal atau Kondisi Patologis? (Sebuah Laporan Kasus) - Alhayu, Yurina; Rahmayanti, Febrina; Astuti, Ambar Kusuma (Dentika: Dental Journal, 2021)
Various normal and pathologic findings might occasionally be found on the tongue and might confuse some patients and clinician due to its atypical presentation. This case report aimed to present a case report of multiple oral findings related to variants of normal and pathological findings on the tongue: geographic tongue, fissured tongue, and central papillary atrophy. A 53-year-old male patient came to Universitas Indonesia Dental Hospital for a dental check-up. Objective examination in the tongue showed depapilated areas surrounded by keratinized lining in the ventral and lateral left and right area of the tongue, multiple fissures in all over the dorsum of the tongue, and an ovoid redness area in the middle of 2/3 posterior dorsum part of the tongue. All those findings were asymptomatic. Those clinical findings were diagnosed as geographic tongue, fissured tongue, and central papillary atrophy. This case presents unique multiple variants of normal and pathological findings in the tongue. It is important to an oral health professional to have knowledge and ability to determine normal anatomy, variants of normal and pathological lesions. Patients should be informed and educated about oral mucosa normal variations and related clinical findings so they would not develop unnecessary anxiety. Keywords: central papillary atrophy, fissured tongue, geographic tongue, normal variations